Meningkatkan kemampuan sosial emosional anak usia 5-6 tahun melalui kegiatan market day di RA Tarbiyatul Akhlaq Wedoroanom - Fauziyah, Nabiatul Luaili; Siti Mufarrochah (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
Social emotional development of children aged 5-6 years includes three aspects of indicators namely self-awareness, attitude of responsibility and prosocial attitude. In this social-emotional development, the proximate attitude has nine sub-indicators in it. This RA Tarbiyatul Akhlaq institution has a background of students who are not optimal in their social emotional development, especially in their prosocial attitudes. For this reason, this Market Day activity is one of the playing activities by selling which can support increasing social emotional development. The research method used in this study is a type of qualitative research with a descriptive approach. The data collection techniques used were participant observation, in-depth interviews and documentation. While the data analysis uses the method of technical triangulation, which combines data obtained from observation, interview and documentation methods. Based on the research conducted by the researchers, it can be concluded that with the Market Day activity, the social emotional development of children aged 5-6 years can develop as expected, but there are some children who are still starting to develop, this is because there are several factors inhibiting their development.